Orofacial characteristics of the very low-birth-weight preterm infants - Dóris Rocha Ruiz (Jornal de Pediatria, 2021)
Objective: To evaluate the orofacial characteristics of very low-birth-weight preterm infants through anthropometric facial measures, orofacial anteroposterior analysis and the relationship between the gum pads. Method: Orofacial examinations was performed in 154 infants, classified into two groups: Group A comprised 54 very low-birth-weight infants who were examined after clinical stabilization and before hospital discharge, and Group B comprised 100 full-term infants. Results: The average anthropometricmeasurements in millimetres for Group A and Group B were as follows: upper third:30.2 and 31.1; middle third: 24.2 and 25.9; lower third: 27.6 and 29.9; facial width: 64.8and 81.4. Regarding the orofacial anteroposterior analysis, the results showed that in99% of these infants, the mandible was in a retrognathic position relative to the maxilla.Group A and Group B had the following distributions of the relationship between thegum pads: overbite-overjet: 43% and 77%; overjet: 39% and 17%; open bite: 15% and3%; end-to-end: 2% and 1%; overbite: both 2%. Conclusion: The very low-birth-weight preterm infants showed the upper third with the highest values in the facialharmony analysis, followed by the lower third and the middle third; and exhibited themandible in a retrognathic position relative to the maxilla, and with overbite-overjet themost prevalent type of gum pad relationship. The study emphasizes the importance of orofacial examination during neonatal hospitalization and the investigation of birth weight and gestational age in a multidisciplinary therapeutic approach that includes orofacial neonatal evaluation and actions that promote oral health, besides foster follow-up studies.